2020
DOI: 10.1038/s41467-020-19984-3
|View full text |Cite
|
Sign up to set email alerts
|

Pathway engineering in yeast for synthesizing the complex polyketide bikaverin

Abstract: Fungal polyketides display remarkable structural diversity and bioactivity, and therefore the biosynthesis and engineering of this large class of molecules is therapeutically significant. Here, we successfully recode, construct and characterize the biosynthetic pathway of bikaverin, a tetracyclic polyketide with antibiotic, antifungal and anticancer properties, in S. cerevisiae. We use a green fluorescent protein (GFP) mapping strategy to identify the low expression of Bik1 (polyketide synthase) as a major bot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 46 publications
(51 reference statements)
2
18
0
Order By: Relevance
“…By expressing the aurZ and aurJ genes in addition to PKS12 in a S. cerevisiae strain carrying PPTase from Aspergillus fumigatus, Rugbjerg et al achieved the recombinant production of 1.1 mg/l rubrofusarin [34]. More recently, Zhao et al demonstrated how S. cerevisiae could be employed both for the whole pathway validation and engineered for an improved recombinant production of bikaverin, a red-colored tetracyclic polyketide with antibacterial and anticancer activities [35]. The authors first introduced four elements from a putative gene cluster for bikaverin synthesis, which included Type I PKS Bik1, FAD-dependent monooxygenase Bik2, O-methyltransferase Bik3, permease Bik6, and PPTase from Fusarium fujikuroi, as well as npgA from A. nidulans, into the S. cerevisiae [35].…”
Section: Polyketidesmentioning
confidence: 99%
See 3 more Smart Citations
“…By expressing the aurZ and aurJ genes in addition to PKS12 in a S. cerevisiae strain carrying PPTase from Aspergillus fumigatus, Rugbjerg et al achieved the recombinant production of 1.1 mg/l rubrofusarin [34]. More recently, Zhao et al demonstrated how S. cerevisiae could be employed both for the whole pathway validation and engineered for an improved recombinant production of bikaverin, a red-colored tetracyclic polyketide with antibacterial and anticancer activities [35]. The authors first introduced four elements from a putative gene cluster for bikaverin synthesis, which included Type I PKS Bik1, FAD-dependent monooxygenase Bik2, O-methyltransferase Bik3, permease Bik6, and PPTase from Fusarium fujikuroi, as well as npgA from A. nidulans, into the S. cerevisiae [35].…”
Section: Polyketidesmentioning
confidence: 99%
“…More recently, Zhao et al demonstrated how S. cerevisiae could be employed both for the whole pathway validation and engineered for an improved recombinant production of bikaverin, a red-colored tetracyclic polyketide with antibacterial and anticancer activities [35]. The authors first introduced four elements from a putative gene cluster for bikaverin synthesis, which included Type I PKS Bik1, FAD-dependent monooxygenase Bik2, O-methyltransferase Bik3, permease Bik6, and PPTase from Fusarium fujikuroi, as well as npgA from A. nidulans, into the S. cerevisiae [35]. With the resulting strain, the authors tested the essentiality of each element and validated the order of the biocatalytic reactions (see the detailed reaction route in Figure 4 in [35]).…”
Section: Polyketidesmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study by Boeke and co‐workers [135] demonstrated the viability of establishing a heterologous expression system and subsequent enzyme/metabolic engineering for fungal polyketide production in S. cerevisiae (Scheme 33). Bikaverin ( 7.33 ), a red‐pigmented tetracyclic xanthone with antibiotic and immunosuppressive activities, [136] was used as a case study.…”
Section: Construction Of Polycyclic Ringsmentioning
confidence: 99%